Contemplating Chineseness in 临摹 lapping emulations - Hong, Shu-ying (Nanyang Technological University, 2021)
临摹 (linmo) Lapping Emulations adopts a process-led investigation to articulate the nuances and complexities of an unstable and protean cultural identity. Ruminating upon my lived experience as part of the Chinese diaspora in Singapore, I begin to conjure new manners of image-making, which include improvised darkroom techniques, as well as photographic and editing experimentations. The adapted techniques seek to encapsulate the unpredictability and fluidity of identity negotiation and extension. Concurrently, such reflections are continually challenged and clarified by my research on the Chinese diaspora, history and culture in Singapore. Thus, I propose that Chineseness is an aggregate of cultural subjectivities and by-product of human sociality.